Challenges in legal translation - revisited - Simonnas, Ingrid (Linguistica (Ljubljana), 2013)
The aim of this paper is to discuss challenges in legal translation from the view of a teacher who evaluates the work of semi-professional translators in a special setting. Recurrent translation errors may subsequently be used as a pedagogical resource in specialised translator training. The observation of recurrent challenges confronting the candidates in legal translation and the absence of formal translator training programs are the reasons why NHH now offers an on-line course in legal translation, JurDist, focusing i.a. on useful translation strategies.
Keywords: e-cours; erreurs de traduction; law; napake; Norveška; pravna terminologija; pravo; prevajalske strategije; prevajanje; spletni tečaji; stratégies de traduction; terminologie juridique; textes juridiques; traduction; translation